MAJAPAHIT AND THE CONTEMPORARY KINGDOMS: INTERACTIONS AND VIEWS: MAJAPAHIT DAN NEGERI-NEGERI SEZAMAN: INTERAKSI DAN PANDANGAN - Munandar, Agus Aris (Berkala Arkeologi, 2020)
Abstract This study discusses the interactions between Majapahit and other kingdoms from a contemporary time in Nusantara, Southeast Asia, India, and China and vice versa. The aim is to formulate the interaction between Majapahit and contemporary kingdoms and vice versa based on existing data. This is an ancient historical study that was conducted in three stages, namely: collecting data contained in written sources such as inscriptions, literary works, and Chinese Chronicles, and archaeological data. The second stage was a data analysis by linking data from written sources with other data, to look for elements that support each other, and always refer to the phenomenon of the study framework. The third stage included an interpretation to gain conclusions. According to the data analysis by examining Majapahit's contemporary regions and kingdoms, it turned out that the kingdom applied the basic concept of Tri Angga which refers to the macrocosm concept of Tri Loka. Majapahit's relationship with India is not as dynamic as that of China, instead, there is a view that India is religiously no longer a reference to Hinduism and Buddhism. Abstrak Kajian ini dilakukan berkenaan interaksi antara Majapahit dengan negeri-negeri lain pada masa yang sama di kepulauan Nusantara, Asia Tenggara, India, Â dan Cina dan sebaliknya. Â Pemahaman yang hendak diperoleh adalah merumuskan perihal interaksi antara Majapahit dengan negeri-negeri sezaman dan sebaliknya. Telaah yang dilakukan berada dalam ranah sejarah kuno dengan tiga tahap kajian, yaitu mengumpulkan data sumber tertulis seperti prasasti, karya sastra dan Berita Cina, dan data arkeologis. Tahap kedua melakukan analisis dengan mengaitkan data sumber tertulis dengan data yang lain, untuk mencari elemen yang saling mendukung dan mengacu kepada fenomena kerangka kajian ini. Tahap ketiga adalah penarikan interpretasi untuk mengarah kepada kesimpulan. Berdasarkan kajian ini, diketahui bahwa dalam memandang daerah dan kerajaan yang berkembang sezaman, ternyata Majapahit menerapkan konsep dasar Tri Angga yang mengacu kepada konsep makrokosmos Tri Loka. Hubungan Majapahit dengan India tidak sedinamis dengan Cina, malahan terdapat pandangan bahwa secara religius India bukan lagi menjadi acuan keagamaan Hindu dan Buddha.